Evaluation of sports nutrition knowledge of New Zealand premier club rugby coaches - Zinn, C.; Schofield, G. M.; Wall, C. (International Journal of Sport Nutrition and Exercise Metabolism, 2006)
Little is known about if and how team coaches disseminate nutrition information to athletes. In a census survey, New Zealand premier rugby coaches (n = 168) completed a psychometrically validated questionnaire, received by either Internet or standard mail (response rate, 46%), identifying their nutrition advice dissemination practices to players, their level of nutrition knowledge, and the factors determining this level of knowledge. The majority of coaches provided advice to their players (83.8%). Coaches responded correctly to 55.6% of all knowledge questions. An independent t-test showed coaches who imparted nutrition advice obtained a significantly greater score, 56.8%, than those not imparting advice, 48.4% (P = 0.008). One-way ANOVA showed significant relationships between total knowledge score of all coaches and qualifications [F(1,166) = 5.28, P = 0.001], own knowledge rating [F(3,164) = 6.88, P = 0.001] and nutrition training [F(1,166) = 9.83, P = 0.002]. We conclude that these rugby coaches were inadequately prepared to impart nutrition advice to athletes and could benefit from further nutrition training.